2020
DOI: 10.5194/egqsj-69-33-2020
|View full text |Cite
|
Sign up to set email alerts
|

The genesis of Yedoma Ice Complex permafrost – grain-size endmember modeling analysis from Siberia and Alaska

Abstract: Abstract. The late Pleistocene Yedoma Ice Complex is an ice-rich and organic-bearing type of permafrost deposit widely distributed across Beringia and is assumed to be especially prone to deep degradation with warming temperature, which is a potential tipping point of the climate system. To better understand Yedoma formation, its local characteristics, and its regional sedimentological composition, we compiled the grain-size distributions (GSDs) of 771 samples from 23 Yedoma locations across the Arctic; sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 57 publications
4
49
0
Order By: Relevance
“…Nevertheless, several studies (e.g. Mackay, 1983;Murton and French, 1994;Kotler and Burn, 2000;Schwamborn et al, 2006;Fritz et al, 2012) have shown that δ 18 O and δD isotopes in intra-sedimental ice can still reflect environmental and climatic changes when considered with caution and/or focused on pore ice Porter and Opel, 2020). Higher δ 18 O and δD but lower d values are found in MIS 3 compared to MIS 2 (Figs.…”
Section: Intra-sedimental Ice Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, several studies (e.g. Mackay, 1983;Murton and French, 1994;Kotler and Burn, 2000;Schwamborn et al, 2006;Fritz et al, 2012) have shown that δ 18 O and δD isotopes in intra-sedimental ice can still reflect environmental and climatic changes when considered with caution and/or focused on pore ice Porter and Opel, 2020). Higher δ 18 O and δD but lower d values are found in MIS 3 compared to MIS 2 (Figs.…”
Section: Intra-sedimental Ice Characteristicsmentioning
confidence: 99%
“…Cryostructures of intra-sedimental ice as well as its stablewater-isotope composition host information of past freezing conditions (e.g. Dereviagin et al, 2013;Schwamborn et al, 2006). The stable-isotope composition of wedge ice is more often used in palaeoclimate studies and serves as a proxy for winter climate conditions and moisture sources because the wedge ice derives mainly from winter precipitation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, modern ice-scouring process can hardly affect the outer shelf sediments at >200 m depth. Furthermore, coarse-grained sediments can be exported from eroding Siberian Yedoma Ice Complex coastlines [66][67][68] or rather transported via lateral brine injections produced by bottom dense-water eddies [69].…”
Section: Grain Size Distribution Along the Studied Profilementioning
confidence: 99%
“…Amphitheater‐shaped slump hollows are 30–50 m wide and are characterized by (1) their concave profile of collapsed banks and (2) highly degraded conical polygons (Figure 1) with wide troughs referred to as “baydjarakhs” (Soloviev, 1973). This ice‐rich permafrost is characterized by its medium and/or fine sand ( D 50 200–300 µm) and silty material ( D 50 18–30 µm) of Quaternary lacustrine or aeolian (loessic) origin (Schirrmeister et al., 2020; Soloviev, 1973). These sediments contain ∼30%–40% of ice by volume, in addition to large syngenetic ice wedges (Strauss et al., 2017; Ulrich et al., 2014).…”
Section: Introductionmentioning
confidence: 99%